Women's Schooling, Home Teaching, and Economic Growth - Behrman, Jere R.; Foster, Andrew D.; Rosenzweig, Mark R.; Vashishtha, Prem (Journal of Political Economy, 1999)
The hypothesis that increases in the schooling of women enhance the human capital of the next generation and thus make a unique contribution to economic growth is assessed on the basis of data describing green revolution India. Estimates are obtained that indicate that a component of the significant and positive relationship between maternal literacy and child schooling in the Indian setting reflects the productivity effect of home teaching and that the existence of this effect, combined with the increase in returns to schooling for men, importantly underlies the expansion of female literary following the onset of the green revolution.